2022
DOI: 10.1002/lio2.728
|View full text |Cite
|
Sign up to set email alerts
|

Non‐coding RNA and cholesteatoma

Abstract: Objective: Cholesteatoma is a challenging chronic pathology of the middle ear for which pharmacologic therapies have not been developed yet. Cholesteatoma occurrence depends on the interplay between genetic and environmental factors while master regulators orchestrating disease progression are still unknown. Therefore, in this review, we will discuss the diagnostic and therapeutic potential of non-coding RNAs (ncRNA) as a new class of regulatory molecules. Methods:We have comprehensively reviewed all articles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Middle ear cholesteatoma is a relatively common disease in otolaryngology [ 20 ], the pathogenesis and mechanisms of which have been drawing growing attention. Numerous studies revealed the roles of miRNAs in the formation and progression of cholesteatoma [ 9 , 10 ].In the present study, we identified 121 significantly differentially expressed miRNAs in acquired retraction pocket cholesteatoma tissues via small RNA sequencing. Among them, 56 miRNAs were upregulated, and 65 miRNAs were downregulated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Middle ear cholesteatoma is a relatively common disease in otolaryngology [ 20 ], the pathogenesis and mechanisms of which have been drawing growing attention. Numerous studies revealed the roles of miRNAs in the formation and progression of cholesteatoma [ 9 , 10 ].In the present study, we identified 121 significantly differentially expressed miRNAs in acquired retraction pocket cholesteatoma tissues via small RNA sequencing. Among them, 56 miRNAs were upregulated, and 65 miRNAs were downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…Several research suggested the genetic associations of cholesteatoma in syndromic and familial forms [7,8]. Also, researchers have recently paid attention to the role of non-coding RNAs in cholesteatoma pathogenesis which have certain therapeutic potential [9,10]. Complete removal of the lesion, preservation of normal middle ear mucosa, and restoration of the middle ear ventilation and drainage system during surgery help reduce the recurrence of cholesteatoma [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Although cholesteatoma has been recognized for more than three centuries [20], the nature of this disorder has yet not been fully determined, particularly the factors regulating its progression [28]. Some studies revealed that sex predilection for cholesteatoma might be dependent on the expression of female sex hormone receptors in the middle ear that act as an auditory protectant [43].…”
Section: Introductionmentioning
confidence: 99%